Existence and Uniqueness of Solutions of a Class of Singular Parabolic Equations (Journal of Partial Differential Equations, 1994)
We will establish an existence and regularity theory for weak solutions of a class of singular parabolic equations associated with Dirichlet data, whose prototype is u_t - div(|&#8711u|^{p-2}&#8711u) = 0 (1 < p < 2)
Keywords: Existence; regularity; singular; weak solutions; parabolic equations